MAXIMIZING THE YIELD OF THE DEPOSIT INVESTOR BY USING DERIVATIVE PRODUCTES (Third Sector Social Economic Review, 2018)
Existing equity capital and reserves are not sufficient for bank growth. Therefore, they need foreign sources. Along with various foreign resources, deposits are the most important factor for banks. In order to expand their deposit base, to withdraw funding difficulties, to reduce outsourcing costs and to keep large deposit customers banks are interested paying high interest rates when it is needed. However, sometimes it can force banks to give high interest rates to direct deposits. For this reason, it is desired to reach this aim through structured deposits by using various derivative products. On the other hand, the most important driving force behind financial markets and the most important factor affecting the preferences of deposit investors are the desire to earn from the investors' assets and the magnitude of this gain. Among the many types of banking derivative transactions, options and swap transactions are the most used for this purpose. This type of product is mostly used by commercial and institutional investors, and it is seen that this type of savings are started to be prefered by natural people. The main purpose of using derivative products is to obtain both interest and installment income by option, keeping some of the deposits in TL and keeping part of them in foreign exchange or keeping the whole in the same currency.In this study; maximization of returns by using structured financial products based on deposits to increase returns by utilizing financial market expectations without the risk of losing the owners of the savings is searched.
Keywords: Deposit; Derivatives; Options; Swaps; DCD; swap deposit.